2016
DOI: 10.1161/strokeaha.115.011749
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Acute Stroke

Abstract: Background and Purpose— Sleep-disordered breathing is common among patients with stroke resulting in 4- to 6-fold higher prevalence of obstructive sleep apnea (OSA). We prospectively evaluated clinical characteristics and laboratory markers of inflammation and coagulability associated with OSA severity during the acute post stroke period. Methods— Consecutive patients admitted to the department of Neurology after an acute ischemic stroke were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 35 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…After reviewing the title and abstract of each article, 99 were excluded for definitive reasons. After reading the full text of the rest 72 potential articles, 25 were further excluded, leaving 47 qualified articles in this meta-analysis according to the preset inclusive criteria [1258]. Because 9 articles provided data by OSAS severity, 1 article by hypertension and 1 article by obesity, there were a total of 59 independent studies involving 2857 OSAS patients and 2115 controls in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the title and abstract of each article, 99 were excluded for definitive reasons. After reading the full text of the rest 72 potential articles, 25 were further excluded, leaving 47 qualified articles in this meta-analysis according to the preset inclusive criteria [1258]. Because 9 articles provided data by OSAS severity, 1 article by hypertension and 1 article by obesity, there were a total of 59 independent studies involving 2857 OSAS patients and 2115 controls in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNF-alpha) is a key modulator of systematic inflammation [810], and TNF inhibition has proven to ameliorate the progression of OSAS [11]. Moreover, some researchers have observed a significant high level of circulating TNF-alpha in OSAS patients vis-à-vis healthy individuals [1218], whereas others did not [19, 20]. The probable causes are multifaceted, relating to statistical power, research design, genetic heterogeneity or dietary habit.…”
Section: Introductionmentioning
confidence: 99%
“…Increased PAI-1 activity was associated with sleep-disordered breathing, possibly contributing to increased vascular risk [ 167 ]. A previous study indicated that PAI-1 levels were significantly higher in OSA subjects than controls and PAI-1 positively correlated with AHI index [ 168 ].…”
Section: Complex Connections Among Osa Dpn and T2dmentioning
confidence: 99%
“…Its prevalence in the general population in North America may be up to 30% in men and 15% in women [ 1 , 2 ]. Patients with untreated OSA are at increased risk for metabolic dysfunction, pulmonary hypertension, arrhythmias, fatal myocardial infarction, and ischaemic stroke [ 3 6 ]. The first-line treatment for OSA is continuous positive airway pressure (CPAP), good compliance with which can lead to better outcomes in areas such as quality of life and cardiovascular health [ 7 ].…”
Section: Introductionmentioning
confidence: 99%